Formulasi Hukum Pidana Korupsi di Indonesia - Lestari Lumban Batu; Zoan Gaharu Perangin-Angin; Maulana Ibrahim; Reh Bungana Br Perangin-Angin (Sharia Journal and Education Center Publishing, 2023)
Abstract Corruption is an act carried out with the intention of obtaining profit which is contrary toofficial duties and other facts